Studying the Mechanical and Electrical Properties of Polyester Resin Reinforced with Silica Particals - H. Mohammad, Shayma. (Journal of Engineering and Sustainable Development, 2013)
A study has been made on the mechanical properties of polyester resin matrix reinforced with weight fraction (10,20, 30&40) % of silica particles. The specimens were subjected to a tensile test bending test (three-point method), and hardness test . The experimental results indicate that the tensile strength of the matrix material was found to be significantly higher than those of the composite material (36%,36.1%,52%,57.5) while the young modulus of matrix material was found to be less than of composite material (14%,33%,42%, 45%). The test result also indicates that the flexural strength of the matrix material was found to be significantly higher than those of the composite material (6%,27%,29%,51) while the young modulus of matrix material was found to be less than of composite material(41%,50%,57.6%, 63%). the hardness of the composite materials is significantly higher than those of the matrix material (20%,28.6%,34%,43%) the enhancement in these properties is found to be directly proportional to the weight fraction of reinforcement materials. Test results also indicate that the electrical conductivity increased with increasing the silica concentrations.